Pengaruh Game Free Fire terhadap Kemampuan Bersosialisasi Anak - Hambesi, Nurhasana; Febrianin, Sindi; Dunda, Paulina; Nurfadilah, Nurfadilah; Dama, Yunus (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to examine the influence of the digital game Free Fire on children’s socialization skills. Online games such as Free Fire are increasingly popular among children and adolescents; however, their impact on social aspects remains debatable. The research method employed was quantitative with a survey approach involving 100 elementary and junior high school students who actively play Free Fire. Data were collected through questionnaires and interviews, then analyzed using descriptive statistical analysis and simple regression. The results indicate a significant influence between the intensity of playing Free Fire and children’s socialization skills. The higher the frequency of playing, the lower the level of face-to-face social interaction among children. Nevertheless, it was also found that in certain contexts, this game can serve as a medium for children to form online communities and friendships. This study concludes that Free Fire exerts a dual influence on children’s socialization skills, depending on the duration of play and the context of use. It is recommended that parents and educators guide children in managing their playtime to prevent disruption of their social development